2020
DOI: 10.3389/fmicb.2020.00562
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Metabolic, and Cellular Characterization of a FtsZ Inhibitor Effective Against Burkholderia cenocepacia

Abstract: There is an urgent need for new antimicrobials to treat the opportunistic Gram-negative Burkholderia cenocepacia, which represents a problematic challenge for cystic fibrosis patients. Recently, a benzothiadiazole derivative, C109, was shown to be effective against the infections caused by B. cenocepacia and other Gram-negative and-positive bacteria. C109 has a promising cellular target, the cell division protein FtsZ, and a recently developed PEGylated formulation make it an attractive molecule to counteract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…The compound was active at a concentration 128-fold lower than the MIC, and it greatly inhibited the formation of the bacterial biofilm in vitro at 0.125 μg/mL. These results showed increased activity of C109 in S. aureus biofilm inhibition compared to that previously reported against B. cenocepacia [ 24 , 25 ], confirming the great potentiality of the molecule against this microorganism [ 26 ]. Moreover, S. aureus biofilms were visualized by confocal laser scanning microscopy, highlighting significant differences in the biofilm structure of C109-treated cells compared to the untreated control.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The compound was active at a concentration 128-fold lower than the MIC, and it greatly inhibited the formation of the bacterial biofilm in vitro at 0.125 μg/mL. These results showed increased activity of C109 in S. aureus biofilm inhibition compared to that previously reported against B. cenocepacia [ 24 , 25 ], confirming the great potentiality of the molecule against this microorganism [ 26 ]. Moreover, S. aureus biofilms were visualized by confocal laser scanning microscopy, highlighting significant differences in the biofilm structure of C109-treated cells compared to the untreated control.…”
Section: Discussionsupporting
confidence: 65%
“…It has been previously demonstrated that C109 targets the FtsZ protein of B. cenocepacia and of P. aeruginosa , blocking their GTPase and polymerization activities [ 24 , 26 ]. To assess C109 activity against the purified FtsZ of S. aureus , the wild type and a previously described more stable deleted version of the protein (12-316aa, ΔFtsZ) [ 31 ] were expressed and purified, as described in Section 4 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations